MixSoy Analisis Implementasi dan Keberlanjutan Bisnis MixSoy di Kota Palembang - sam pramudana gunawan; Charisma Ayu Pramuditha (MDP Student Conference, 2026)
MixSoy is a trendy beverage made from soy milk as its main ingredient. MixSoy has three main flavor variants: manggo, strawberry, and avocado. MixSoy conduct promotions throught social media, particularly instagram, as well as endorsements with influencers in Palembang, and also release hamper variants during major holidays. Based on its business performance results, MixSoy is cosidered capable of competing and continuing to grow in the future.